Analysis of Information Technology Service Management Using ITIL V3 Domain Service Operation at Company XYZ - Shidqi, Shafirina Arsydini; Adha, Fatihilal; Novendri, Alia; Artanti, Freda Widya; Widadi, Wiwit Puja Marga; Subarkah, Fakhry; Tarwoto, Tarwoto (International Journal of Informatics and Information Systems, 2023)
The rapid development of information technology and excellent technology services have become the aspiration for everyone, organizations, institutions, and universities to support their activities, facilitate their tasks, and streamline their business processes. An enterprise organization needs to adapt to the current information technology trends. Managing IT services is a centralized method focusing on consumers' perspective of IT services towards a company's business. XYZ Company has implemented information technology specifically designed for users to manage service activities and process company administrative data. Service Operation is a lifecycle phase covering all day-to-day operations of IT service management. Based on research results on 3 processes, namely Event Management, Request Fulfillment, and Problem Management, there is a need to enhance the hardware, software, and infrastructure requirements to adequately meet the needs of XYZ Company for more effective work. Additionally, the need for implementing Standard Operating Procedures (SOP) and appropriate modules for employees is crucial to enhance their efficiency in utilizing information technology.